Лучшие помощники
- Megamozg 2190 б
- Matalya1 1800 б
- DevAdmin 1695 б
- arkasha_bortnikov 860 б
- Dwayne_Johnson 845 б
3^(5x+1)+3^(5x-1)=30
(3^5x)*3^1+(3^5x)*(3⁻¹)=30
3*(3^5x)+(1/3)*(3^5x)=30
(3^5x)*(3+1/3)=30
(3^5x)*(10/3)=30
3^5x=9
3^5x=3²
5x=2
x=0,4
x/(x+1), 0,4/(0,4+1)=0,4/1,4=0,2/0,7=2/7
(3^5x)*3^1+(3^5x)*(3⁻¹)=30
3*(3^5x)+(1/3)*(3^5x)=30
(3^5x)*(3+1/3)=30
(3^5x)*(10/3)=30
3^5x=9
3^5x=3²
5x=2
x=0,4
x/(x+1), 0,4/(0,4+1)=0,4/1,4=0,2/0,7=2/7
0
·
Хороший ответ
16 декабря 2022 22:09
Остались вопросы?
Все предметы